Analisis Buku Teks Kimia Dasar Berdasarkan Multiple Representasi Konsep Korosi - Ovilia, Ghea; Wiji, Wiji; Mulyani, Sri; Widhiyanti, Tuszie (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
Chemical representations and the connections among macroscopic, sub-microscopic, and symbolic levels are fundamental to meaningful chemistry learning. However, the quality and coherence of these representations in instructional materials often determine how effectively students construct conceptual understanding. This study aimed to investigate the types and interconnections of chemical representations related to corrosion presented in widely used general chemistry textbooks. A qualitative content analysis was conducted on five textbooks using an adapted framework from Gkitzia, which included the type of representation (C1), interpretation of surface features (C2), relatedness to the text (C3), caption quality (C4), and degree of correlation across multiple representations (C5). A total of 40 corrosion-related representations were identified. The analysis showed that symbolic representations were the most frequently used, although textbooks generally portrayed corrosion through macroscopic, real-world examples. Eight sets of multiple representations were found to demonstrate adequate coherence among macroscopic, sub-microscopic, and symbolic levels, effectively illustrating both the corrosion process and its prevention. Overall, the five textbooks presented the concept of corrosion with reasonable alignment across representational forms. These findings contribute to the improvement of chemistry education by informing educators and textbook authors about the strengths and limitations of current representational practices. The results also offer empirical support for implementing multiple-representation-based instruction to enhance students’ conceptual understanding and ability to visualize and interpret corrosion phenomena.